The Cash Flow Ratio Analysis To Assess The Financial Performance Of PT Mitrabara Adiperdana Tbk, Period 2015-2019 - Nurul Monika; Setyo Riyanto (Journal of Social Science, 2020)
Human resources are the foremost vital component in an organization, since it includes a part as a driver and controller of organizational exercises. All organizations will certainly make each effort to advance the shape and progress the quality of worker execution with awesome human asset administration. Great employee execution will be fulfilled in case the company can recognize any components that can make strides employee execution, one of the factors that can impact employee performance is work motivation, and the work environment. This composing points to decide the impact of work motivation on employee performance, and decide the impact of the work environment on employee performance. By giving great inspiration, giving more consideration and accomplishment to employees, and giving a work environment that can back employee performance, to diminish worker turnover within the company. And of course, employees will be more faithful to the company.